2014
DOI: 10.1111/anti.12088
|View full text |Cite
|
Sign up to set email alerts
|

Women, Communities, Neighbourhoods: Approaching Gender and Feminism within UK Urban Policy

Abstract: In recent years some commentators have looked at successive waves of UK urban policy from the perspective of gender, although these commentaries have been somewhat marginal within wider discussions of urban policy and politics. This article seeks to make the case for a renewed emphasis on gender, which moves beyond tracing the role of men and women in relation to urban policy programmes, in two particular ways. First it is argued that a more sophisticated analysis of the gendered nature of urban governance is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 55 publications
(99 reference statements)
1
24
0
1
Order By: Relevance
“…Recent feminist research has suggested that it is time to revisit feminist principles in urban studies and (re) notice sexism and patriarchy and to “get angry again” (e.g. Douglas ; Gill , ; Jupp ; Peake ; Valentine et al ). Scholars have also demanded that we pay attention (in non‐voyeuristic ways) to pressing racial inequalities and violences in cities and urban politics (e.g.…”
Section: Salient Silences: Gender Race and Feminism In Urban Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent feminist research has suggested that it is time to revisit feminist principles in urban studies and (re) notice sexism and patriarchy and to “get angry again” (e.g. Douglas ; Gill , ; Jupp ; Peake ; Valentine et al ). Scholars have also demanded that we pay attention (in non‐voyeuristic ways) to pressing racial inequalities and violences in cities and urban politics (e.g.…”
Section: Salient Silences: Gender Race and Feminism In Urban Researchmentioning
confidence: 99%
“…They tend to focus on markets and a narrowly construed state, whereas analytics that attend to everyday life, racialization, gender, subjects and subjectivities, spaces of encounter, the “global intimate”, bodies, households, are marginalized (e.g. Isoke 2013; Jupp ; McKittrick ; Mountz and Hyndman ). Mainstream political economy may unintentionally reproduce binaries (e.g.…”
Section: Salient Silences: Gender Race and Feminism In Urban Researchmentioning
confidence: 99%
See 3 more Smart Citations